Taxocenosis of mollusks and crustaceans on roots of rhizophora mangle (rhizophoraceae) at cispatá bay, córdoba, colombia (2013)
Despite the existing knowledge on the ecology of mangroves at Cispatá Bay, few studies have focused on the association of invertebrates on red mangrove roots, so between December 2010 and September 2011, it was characterized taxocenosis of mollusks and crustaceans on roots of Rhizophora mangle in two study sites at Cispatá Bay, Colombia. For the collections of biological material were randomly taken three red mangrove roots with a diameter. Mollusks and crustaceans were obtained from the root surface with a scraping knife then were removed and fixed in 10 % formalin for later identification to species using specialized taxonomic keys. Of the 12289 individuals collected in the four samples, 10470 belonged to the phylumMollusca (85,2 %) and the remaining 1819 to subphylum Crustacea (14,8 %). For mollusks were identified 14 species distributed in 11 families and two classes; Bivalvia and Gastropoda. For crustaceans were identified 24 species distributed in 16 families and four orders; Sessillia, Decapoda, Isopoda and Amphipoda. In both sectors sampling Mytella charruana, Balanus eburneusand Crassostrea rhizophorae were the most important species in terms of abundance, however mollusks like M. charruana and B. eburneus have a great ability to adapt and adjust to changing hydroclimatic, which was reflected in the dominance of these species in the sector with the greatest influence Sinu River. The presence of crustaceans Petrolisthes armatus and Aratus pisonii in the sector with more proximity to the Caribbean Sea indicate that are species with great mobility and physiological adaptation mechanisms.TAXOCENOSIS DE MOLUSCOS Y CRUSTÁCEOS EN RAÍCESDE Rhizophora mangle (RHIZOPHORACEAE)EN LA BAHÍA DE CISPATÁ, CÓRDOBA, COLOMBIAA pesar del conocimiento existente sobre la ecología de los manglares en la bahía de Cispatá, pocos estudios han sido enfocados en invertebrados asociados a las raíces del mangle rojo. Entre diciembre 2010 y septiembre 2011, se evaluó la estructura de los ensamblajes de moluscos y crustáceos asociados a las raíces de Rhizophora mangle en dos sectores de muestreo de la bahía de Cispatá, Colombia. Para la recolección del material biológico se tomaron al azar tres raíces de mangle homogéneas en cuanto al diámetro. Los organismos fueron obtenidos de la raíz raspando la superficie con un cuchillo, luego fueron separados y fijados en formalina al 10% para su posterior identificación. De los 12289 individuos recolectados en los cuatro muestreos, 10470 pertenecieron al phylum Mollusca (85,2%) y los restantes 1819 al subphylum Crustacea (14,8%). Para los moluscos se identificaron 14 especies distribuidas en 12 familias y dos clases; Bivalvia y Gastropoda. Para los crustáceos se identificaron 24 especies distribuidas en 16 familias y cuatro órdenes; Sessillia, Decapoda, Isopoda y Amphipoda. En los dos sectores de muestreo Mytella charruana, Balanus eburneus y Crassostrea rhizophorae fueron las especies más importantes en términos de abundancia, no obstante M. charruana y B. eburneus presentan una gran capacidad de adaptación y ajuste a las variaciones hidroclimáticas, mostrándose como especies fuertemente eurihalinas, lo que se relejó en la dominancia de dichas especies en el sector B. La presencia de Petrolisthes armatus y Aratus pisonii indica que son especies de bosques de manglar con gran movilidad y mecanismos de adaptación fisiológicos, lo que justifica su presencia en el sector A.